Shear strength of a soil containing vegetation roots - Ali, F.H.; Osman, Normaniza (2008)
Vegetation can significantly contribute to stabilise sloping terrain by reinforcing the soil: this reinforcement depends on the morphological characteristics of the root systems and the tensile strength of single roots. This paper describes all investigation on the reinforcing effect of soil-root matrix in the laboratory using a modified large shear box apparatus (300 mm X 300 mm). Four different species of plant namely Vertiveria zizanoides, Leucaena leucocephala, Bixa orellana and Bauhinia purpurea were planted in special boxes containing residual soil compacted to a known density. The results show that roots significantly contribute to the increase in soil shear strength. The presence of the roots only affects the apparent cohesion of the soil and no significant change in angle of friction is observed. L. leucocephala shows the outstanding increase in its root strength in which the strength varies with depth and time e.g., under soil suction-free condition (matric suction = 0), the roots have increased the cohesion by 116.6% (0.1 m), 225.0% (0.3 m) and 413.4% (0.5 m) after six months of growth. In twelve months, it is observed that the increase in cohesion is more than three-fold of the six months growth period at 0.1 m depth. The results also indicate that shear strength is influenced by root profile and to some extent, the physiological parameters of the plants.